Factors Affecting Leisure Air Travelers to Choose Sichuan as their Tourism Destination - Ma, Jian Ping (2010)
This study is carried out with the aim to propose recommendations to the Sichuan government and tourism operators to promote the tourism industry in Sichuan after the Wenchuan earthquake in year 2008. By identifying factors influencing leisure air travelers to choose Sichuan as their tourism operators to develop the positioning of and marketing communication strategies for Sichuan. The identification of factors such as destination cost influencing leisure air travelers on low cost airline and the attractiveness of destination factor influencing leisure travelers on full service airlines in choosing Sichuan as their tourism destination will assist the planning of marketing communication messages and marketing strategy to market Sichuan to the different groups of leisure air travelers. The most important contribution of this study is the results on the similarities and differences between the factors influencing leisure air travelers on low cost airline and those on full service airlines to Sichuan where there is limited prior studies in this area.